2016
DOI: 10.1530/joe-16-0064
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes play an etiological role in the podocytopathy of high-fat diet-fed rats

Abstract: Obesity is a risk factor that promotes progressive kidney disease. Studies have shown that an adipocytokine imbalance contributes to impaired renal function in humans and animals, but the underlying interplay between adipocytokines and renal injury remains to be elucidated. We aimed to investigate the mechanisms linking obesity to chronic kidney disease. We assessed renal function in high-fat (HF) diet-fed and normal diet-fed rats, and the effects of preadipocyte- and adipocyte-conditioned medium on cultured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…It remains unclear whether this osteophyte formation itself can cause further joint degeneration and cartilage loss or is the consequence. After HF diet feeding systemic metabolic alterations are known to increase the fat content, alter adipocytes size and stimulate their pro‐inflammatory cytokine production such as tumor necrosis factor‐α, interleukin‐1β, and interleukin‐6 . These cytokines are not only produced systemically but also locally by different tissues in OA knee joints including the infrapatellar fat pad and the synovial membrane .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear whether this osteophyte formation itself can cause further joint degeneration and cartilage loss or is the consequence. After HF diet feeding systemic metabolic alterations are known to increase the fat content, alter adipocytes size and stimulate their pro‐inflammatory cytokine production such as tumor necrosis factor‐α, interleukin‐1β, and interleukin‐6 . These cytokines are not only produced systemically but also locally by different tissues in OA knee joints including the infrapatellar fat pad and the synovial membrane .…”
Section: Discussionmentioning
confidence: 99%
“…After HF diet feeding systemic metabolic alterations are known to increase the fat content, alter adipocytes size and stimulate their pro-inflammatory cytokine production such as tumor necrosis factor-a, interleukin-1b, and interleukin-6. [45][46][47] These cytokines are not only produced systemically but also locally by different tissues in OA knee joints including the infrapatellar fat pad and the synovial membrane. 6,18,48 In most tissues macrophages are a significant source of inflammatory cytokines, were both BMI and adipocyte size were strong predictors of the percentage of CD68-expressing macrophages.…”
Section: Metabolic Dysregulation Accelerates Injury-induced Joint Degmentioning
confidence: 99%
“…It has been generally recognized that podocyte damage and dysfunction play a pivotal role in the occurrence and progression of ORG. [ 11 12 13 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data have shown that hyperleptinemia often occurred in obese individuals and could induce a lot of pathophysiologic responses which were involved in the inflammatory effect and kidney damage, including podocyte damage, of ORG. [ 12 13 23 24 25 26 ] Therefore, leptin was selected as the inducer to the established cell model in this study. Both animal and cell models provided this study with good platforms for research of pathogenic mechanism of ORG in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation